ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN EKONOMI DI SMA KHZ MUSTHAFA SUKAMANAH TASIKMALAYA - Dicky Ramadhan Sudrajat; Disman Disman; Ikaputera Waspada (FKIP Unswagati, 2021)
AbstractThis study aims to determine and analyze students' critical thinking skills in learning economics. This research is a quantitative research. The method applied in this research is descriptive by collecting data through a questionnaire containing essay questions that have been adjusted to the indicators of critical thinking. The population in this study were students of SMA KHZ Musthafa Sukamanah Tasikmalaya class XI from the science and social studies department with 90 respondents using the Taro Yamane formula. The data collected is then processed. The results of the analysis prove that the students' critical thinking skills fall into the low category. This means that it needs special attention from the teacher so that students' critical thinking skills are better. The results of this study have an implication that the critical thinking skills of students at SMA KHZ Musthafa Sukamanah Tasikmalaya are still low, as evidenced by the average value of critical thinking skills of 40, so that efforts are needed to overcome these problems.Keywords: 21st century skills, Critical thinking skills, Economics subject.